Neuronal Differentiation from Induced Pluripotent Stem Cell-Derived Neurospheres by the Application of Oxidized Alginate-Gelatin-Laminin Hydrogels - Thomas Distler; Ines Lauria; Rainer Detsch; Clemens M. Sauter; Farina Bendt; Julia Kapr; Stephan Rütten; Aldo R. Boccaccini; Ellen Fritsche (Biomedicines, 2021)
Biodegradable hydrogels that promote stem cell differentiation into neurons in three dimensions (3D) are highly desired in biomedical research to study drug neurotoxicity or to yield cell-containing biomaterials for neuronal tissue repair. Here, we demonstrate that oxidized alginate-gelatin-laminin (ADA-GEL-LAM) hydrogels facilitate neuronal differentiation and growth of embedded human induced pluripotent stem cell (hiPSC) derived neurospheres. ADA-GEL and ADA-GEL-LAM hydrogels exhibiting a stiffness close to ~5 kPa at initial cell culture conditions of 37 °C were prepared. Laminin supplemented ADA-GEL promoted an increase in neuronal differentiation in comparison to pristine ADA-GEL, with enhanced neuron migration from the neurospheres to the bulk 3D hydrogel matrix. The presence of laminin in ADA-GEL led to a more than two-fold increase in the number of neurospheres with migrated neurons. Our findings suggest that laminin addition to oxidized alginate—gelatin hydrogel matrices plays a crucial role to tailor oxidized alginate-gelatin hydrogels suitable for 3D neuronal cell culture applications.